Understanding Sibumasu in the context of ribbon continents - C. K. Morley (2018)
© 2018 International Association for Gondwana Research Well-described ribbon continent collision belts, and modern examples, with 2D seismic coverage, particularly Zealandia, provide analogues for the Permo-Triassic development of Sibumasu. Two key parameters for the ribbon continents are their width, and how rifting developed, which in turn impact the structural, metamorphic, igneous, and stratigraphic development of ribbon continents in ways that make them significantly different from the collisional development of major continents. Key characteristics of the tectonics of Sibumasu are: 1) a tendency towards basin inversion during the Late Triassic and possibly Early Jurassic, and mixed thick-skinned and thin-skinned style deformation. 2) Extensional collapse around 215 Ma is an important feature of Sibumasu (particularly in northern Thailand, and probably other areas too). 3) Slab delamination and extension-related decompression melting were probably important mechanisms for generating granites in addition to crustal thickening. 4) Metamorphism is relatively high temperature, lower pressure.